THE CORRELATION BETWEEN THE VOCABULARY MASTERY AND READING COMPREHENSION’S ABILITY OF THE FIFTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Alfahri, Roby; Dahnilsyah, Dahnilsyah; Syarfi, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This correlational research is aimed to find out whether there is a correlation between vocabulary mastery and reading comprehension’s ability of the fifth semester students of English Study Program FKIP-UR. The sample was 28 students selected through cluster random sampling. The instruments used in this research were the vocabulary and reading TOEFL test items. The research finding revealed that the vocabulary mastery test result of the fifth semester students of English Study Program FKIP-UR was at the good level (75), and their reading comprehension’s ability was at good level (69) also. Based on Pearson correlation analysis, it was obtained that the correlation coefficient between the students’ vocabulary mastery and reading comprehension’s ability was 0.876 with the sig. value=0.00. Hence, it could be concluded that there was a very high correlation between the vocabulary mastery and reading comprehension’s ability of the fifth semester students of English Study Program FKIP-UR. As a consequence, the null hypothesis was rejected and alternative hypothesis was accepted.Key Words: Correlation, Vocabulary Mastery, Reading Comprehension’s Ability